Prevention of unintended pregnancy and use of contraception—important factors for preconception care. (1st October 2016) - Kallner, Helena Kopp; Danielsson, Kristina Gemzell
Abstract: Preservation of fertility and optimizing health before pregnancy is becoming increasingly important in societies where childbirth often is postponed. Research shows that as women postpone childbirth they achieve higher levels of education and higher incomes. This leads to advantages for their children and for society. However, as women postpone childbearing they are at risk for contracting conditions which may affect fertility and/or pregnancies, pregnancy outcome, and the newborn child. Preconception counseling is therefore becoming increasingly important. Women are often unaware of the added health benefits of contraception and have the right to be well informed so they can make decisions to fulfill their reproductive desires. Contraception can reduce the risk of unintended pregnancies, ectopic and molar pregnancies, and sexually transmitted infections. In addition, hormonal contraceptives reduce the risk of some types of cancer, dysmenorrhea, heavy menstrual bleeding, and anemia and are a treatment for endometriosis. Contraception should increasingly be looked upon as a means of preserving fertility and optimizing health status before a planned pregnancy. Thus, effective contraception can provide women with a possibility of achieving their long-term reproductive goals, although childbearing is actually postponed. The most effective contraceptive methods are the long-acting reversible contraceptives, which have been shown to be highly effective especially in young women who have difficulties with adherence to user-dependent methods. Therefore, these methods should increasingly be promoted in all age groups.